(untitled) (Marketing Journal, 2025)
The article analyzes the impact of ma rketing strategies on product sales in online marketplaces. It examines the freemium model, live -streaming sales, omni -digital strategies, use of artificial intelligence, and market segmentation. The findings help companies attract new customers, increase sales, and strengthen brand reputation.